2017
DOI: 10.1038/s41598-017-11703-1
|View full text |Cite|
|
Sign up to set email alerts
|

T-cell tolerance and exhaustion in the clearance of Echinococcus multilocularis: role of inoculum size in a quantitative hepatic experimental model

Abstract: The local immune mechanisms responsible for either self-healing or sustained chronic infection are not clear, in the development of E. multilocularis larvae. Here, we developed a suitable experimental model that mimics naturally infected livers, according to the parasite load. We demonstrated that local cellular immunity and fibrogenesis are actually protective and fully able to limit metacestode growth in the liver of low or medium dose-infected mice (LDG or MDG), or even to clear it, while impairment of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 49 publications
1
65
4
Order By: Relevance
“…TIGIT + Treg cells appear uniquely capable of suppressing T h 1-type responses, as opposed to T h 2 responses. (31) T-cell exhaustion actually plays a role in E. multilocularis metacestode growth (6,8) in addition to the well-described immune tolerance mediated by Treg cells and regulatory cytokines in intermediate hosts with chronic infection. (1,2) Although the precise mechanisms remain to be elucidated by further experiments, our findings showed that the treatment with anti-TIGIT mAb reduced the liver metacestode load, together with a significantly increased T h 1-type T-cell response in liver and spleen, including elevated IL-2, IFN-γ, and TNF-α production.…”
Section: Fig 4 In Vitro Tigit Blockade Increases T-cell Response Fomentioning
confidence: 99%
See 2 more Smart Citations
“…TIGIT + Treg cells appear uniquely capable of suppressing T h 1-type responses, as opposed to T h 2 responses. (31) T-cell exhaustion actually plays a role in E. multilocularis metacestode growth (6,8) in addition to the well-described immune tolerance mediated by Treg cells and regulatory cytokines in intermediate hosts with chronic infection. (1,2) Although the precise mechanisms remain to be elucidated by further experiments, our findings showed that the treatment with anti-TIGIT mAb reduced the liver metacestode load, together with a significantly increased T h 1-type T-cell response in liver and spleen, including elevated IL-2, IFN-γ, and TNF-α production.…”
Section: Fig 4 In Vitro Tigit Blockade Increases T-cell Response Fomentioning
confidence: 99%
“…Many studies have shown that cellular immunity affects the development of AE lesions, and that AE is more severe, with a faster course, when there is some degree of impairment of the functional activity of T cells . Persistence of E. multilocularis is associated with a chronic granulomatous inflammation, leading to the disruption of the normal function of T cells, which is nowadays referred to as “functional exhaustion.” Recent reports have also shown that E. multilocularis infection is associated with the expression of “checkpoint” receptors that are known to limit the activity of parasite‐specific lymphocytes. We and others have shown that the receptors programmed cell‐death 1 (PDCD1), 2B4 (SLAMf4, CD244), and lymphocyte‐activation gene 3 (LAG3) are aberrantly expressed during chronic infection, and that they contribute to “exhausted” parasite‐induced T‐cell response and lead to the maintenance of E. multilocularis survival .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that upregulation of PD‐1 on CD4 + CD25 + T cells is associated with immunosuppression in liver of mice infected with E. multiloculari s . Echinococcus multilocularis proliferation and some malignant tumours are both sharing similar features such as local immune evasion, induction of tolerance and disruption of T cell signalling, and T cell exhaustion at late stage of infection . Monoclonal antibodies targeting PD‐1 or PD‐L1 are in clinical use demonstrating high efficacy in lung, colon, head, neck and gastric cancers, in addition to renal cell carcinoma and melanoma …”
Section: Introductionmentioning
confidence: 99%
“…Imbalance of Th1&Th17 and Tregs is crucial for generation of increasing T EMs in T1DM [37]. While some studies have shown that tolerance-inducing therapies can lead to an increase in Tregs in lymphoid and nonlymphoid target tissue, conversely, it is difficult to inhibit T EMs formation in autoimmunity diseases [38].…”
Section: Discussionmentioning
confidence: 99%